Complex evaluation of ecotoxicity and genotoxicity of antimicrobials oxytetracycline and flumequine used in aquaculture - Zounková, Radka; Klimešová, Zdeňka; Nepejchalová, Leona; Hilscherová, Klára; Bláha, Luděk (Environmental toxicology and chemistry, 2011)
Ecotoxicity and genotoxicity of widely used veterinary antimicrobials oxytetracycline and flumequine was studied with six model organisms (Vibrio fischeri, Pseudomonas putida, Pseudokirchneriella subcapitata, Lemna minor, Daphnia magna, Escherichia coli). Overall median effective concentration (EC50) values ranged from 0.22 mg/L to 86 mg/L. Pseudomonas putida was the most sensitive organism (EC50 values for 16-h growth inhibition were 0.22 and 0.82 mg/L for oxytetracycline and flumequine, respectively), followed by duckweed Lemna minor (7-d growth inhibition, EC50 2.1 and 3.0 mg/L) and green alga Pseudokirchneriella subcapitata (4-d growth inhibition, EC50 3.1 and 2.6 mg/L). The least sensitive organism was Daphnia magna (48-h immobilization, lowest-observed-effect concentration [LOEC] of oxytetracycline of 400 mg/L). Oxytetracycline showed limited genotoxicity (SOS-chromotest with Escherichia coli, minimal genotoxic concentration of 500 mg/L), and flumequine was genotoxic at 0.25 mg/L. Based on the reported measured concentrations (MECs) and predicted no-effect concentrations (PNECs), oxytetracycline may be concluded to be of ecotoxicological concern (calculated risk quotient = 8), whereas flumequine seems to represent lower risk.
Keywords: Animals; Oxytetracycline; chemické látky znečišťující vodu; Escherichia coli; Water Pollutants, Chemical; Daphnia; antiinfekční látky; Chlorophyta; Anti-Infective Agents; Aliivibrio fischeri; vodní hospodářství; mutageny; Fluoroquinolones; fluorochinolony; Aquaculture; Pseudomonas putida; Mutagens; zvířata; oxytetracyklin